Interictal hyposexuality in male patients with epilepsy - Silveira Diosely C.; Souza Elizabeth A. P. de; Carvalho José F.; Guerreiro Carlos A. M. (Arquivos de Neuro-Psiquiatria)
The purpose of this study was to compare the serum levels of androgens between hyposexual and non-hyposexual patients with epilepsy. Adult male patients with epilepsy were investigated. Serum levels of testosterone (T) and free-T, estradiol, and sex hormone binding globulin (SHBG) were measured and the free androgen index (FAI) was calculated. While there were no differences between hyposexual and non-hyposexual patients in the serum levels of T, free-T, and estradiol, or to the FAI, the serum levels of SHBG were significantly higher in hyposexual patients than in non-hyposexual patients. Thus, the effects of increased SHBG upon serum levels of testosterone biologically active in patients with epilepsy and hyposexuality were not detected by the methods used in this study. Four (44%) of nine hyposexual patients who were re-evaluated after two years follow-up improved sexual performance. Thus, clinical treatment that results in good seizure control may improve sexual performance in some patients with epilepsy.